Assessment of reproductive performance of Begait cattle in in-situ and ex-situ sites and in different production systems in northern Ethiopia - Gebrekidan, B.; Tegegne, Azage; Regassa, F. (Elsevier, 2016)
Retrospective studies were conducted in Kafta-Humera and Wukro areas of Tigray region of Ethiopia. A retrospective study was carried out on 12 herds consisting 2144 Begait cattle from pastoral and agro-pastoral areas to assess herd composition and calf-crop. To evaluate the reproductive performance, 210 cows were selected randomly from pastoral, agro-pastoral, confinement and crop-livestock production systems. All necessary data of reproductive parameters were collected through questionnaire surveys, group discussions and follow-up observations. SPSS software was applied to analyze the data. The result of the present study showed that the average calf-crop of 53% and 42.1% and annual calf mortality rate of 20.8% and 9.4%, were observed for pastoral and agro-pastoral production systems, respectively. The mean age at first service (AFS), age at first calving (AFC) and calving interval (CI) in months were 34.9, 43.9 and 12.9 in pastoral, 35.9, 45.0 and 14.0 in agro-pastoral, 34.4, 44.9 and 15.0 in confinement and 40.5, 49.5 and 19.6 in crop-livestock production systems, respectively. AFC and CI were significantly (P < 0.05) affected by site and production system. Significantly longer AFS, AFC and CI were noticed in crop-livestock system than in the other 3 production systems. However, CI was not affected by age and parity.